Etching Patterns of Self-Etching Primers in Relation to Shear Bond Strength on Unground Enamel Samples - Lorenz Brauchli; Markus Steineck (MDPI AG, 2021)
It was the intention of the study to evaluate the etching effects of several self-etching primers on unground enamel and their relevance for shear bond strength testing. Seven self-etching primers (Clearfil SE, Futurabond NR, M-Bond, One Coat, Optibond, Transbond SEP+, Xeno III) and a conventional 35% phosphoric gel acid were applied to bovine incisors according to the manufacturer's instructions. All specimens were analyzed by electron microscopy. A visual four-step grading was used for the characterization of the macroscopic (5000×) and microscopic (20,000×) etching patterns. In addition, shear bond strength for all the products was tested with an Instron 3344 after 1000 thermocycles between 5 °C and 55 °C. Statistical analysis was carried out using Kruskal-Wallis with Dunn's post-test and Pearson's correlation coefficient. Very strong etching patterns with well-defined prisms were found for the conventional etching, Transbond SEP+, and to a lesser degree, for Xeno III. Clearfil SE and Futurabond NR revealed moderate etching patterns, and M-Bond, One Coat, and Optibond revealed very weak etching patterns. The bond strength correlated well with the etching patterns. The highest shear strength was obtained with conventional etching and Transbond SEP+, followed by Clearfil SE. Moderate shear bond strengths were found for Xeno III, Futurabond NR, One Coat, and M-Bond, and the lowest were found with Optibond.